US Student Mobility Trends in a Global Context - Bhandari, Rajika (International Higher Education, 2017)
Drawing upon current student mobility data, this article highlights five key developments in the field of international student mobility, with a particular focus on the United States. Trends related to specific international education initiatives are examined, as is the impact of a shifting political climate globally.